Control of general and special physical preparedness of sportsmen is 12-13 years in taekwondo - Bachinskaya N.V.; Koshcheev A.S. (Pedagogìka, Psihologìâ ta Mediko-bìologìčnì Problemi Fìzičnogo Vihovannâ ì Sportu, 2010)
The features of control of general and special physical preparedness of young sportsmen are examined. Considerable part of researches in area of control and training process control in taekwondo is devoted practice of sport of higher achievements. Timely realization of control of physical preparedness for sportsmen will allow expediently to develop physical qualities. It will allow in the future to apply sportsmen on achievement of high and stable sporting results.